LDL-apheresis depletes apoE-HDL and pre-β1-HDL in familial hypercholesterolemia: relevance to atheroprotection - Orsoni, Alexina (The American Society for Biochemistry and Molecular Biology, 2011)
Subnormal HDL-cholesterol (HDL-C) and apolipoprotein (apo)AI levels are characteristic of familial hypercholesterolemia (FH), reflecting perturbed intravascular metabolism with compositional anomalies in HDL particles, including apoE enrichment. Does LDL-apheresis, which reduces HDL-cholesterol, apoAI, and apoE by adsorption, induce selective changes in HDL subpopulations, with relevance to atheroprotection? Five HDL subpopulations were fractionated from pre- and post-LDL-apheresis plasmas of normotriglyceridemic FH subjects (n = 11) on regular LDL-apheresis (>2 years). Apheresis lowered both plasma apoE (−62%) and apoAI (−16%) levels, with preferential, genotype-independent reduction in apoE. The mass ratio of HDL2:HDL3 was lowered from ∼1:1 to 0.72:1 by apheresis, reflecting selective removal of HDL2 mass (80% of total HDL adsorbed). Pre-LDL-apheresis, HDL2 subpopulations were markedly enriched in apoE, consistent with ∼1 copy of apoE per 4 HDL particles. Large amounts (50-66%) of apoE-HDL were removed by apheresis, preferentially in the HDL2b subfraction (−50%); minor absolute amounts of apoE-HDL were removed from HDL3 subfractions. Furthermore, pre-β1-HDL particle levels were subnormal following removal (−53%) upon apheresis, suggesting that cellular cholesterol efflux may be defective in the immediate postapheresis period. In LDL-receptor (LDL-R) deficiency, LDL-apheresis may enhance flux through the reverse cholesterol transport pathway and equally attenuate potential biglycan-mediated deposition of apoE-HDL in the arterial matrix.